Genetic Analysis of Calf Survivability in Gir Crossbreds - MOTE, MAHENDRA GORAKH (Indian Journal of Animal Production and Management, 2024)
Data of Gir crossbred calves, maintained at Research cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri, for a period from 2005 to 2019 was collected to study effect of genetic and non-genetic factors on survivability traits of calf. The traits studied were cumulative survivability within 0 to 15 days, 0 to 30 days, 0 to 90 days, 0 to 180 days and 0 to 365 days. The least square means of cumulative survivability per cent of Gir crossbred calves at 0 to 15, 0 to 30, 0 to 90, 0 to 180 and 0 to 365 days were 83.27±2.16, 75.40±2.57, 62.29±2.99, 53.96±3.16 and 52.16±3.17, respectively. The period of birth had significant (P